Preparation and packaging process of high-performance packaging adhesive for new energy battery CCS busbar device

By using the mixture of PA resin and binder and the addition of spherical microspheres and nano-aluminum nitride in the injection molding of the polyamide (PA) resin in the injection molding of the CCS busbar device of the new energy battery, the problems of weak bonding performance and stress shrinkage in the injection molding of the polyamide (PA) resin are solved, and high-performance packaging glue preparation and process are achieved.

CN119662192APending Publication Date: 2025-03-21ANTIN (FUJIAN) NEW MATERIAL CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411840756.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-13
Publication Date
2025-03-21

AI Technical Summary

Technical Problem

In the prior art, when injection molding of the new energy battery CCS busbar device with polyamide (PA) resin, there are poor problems such as weak bonding performance and cracking after internal stress shrinkage.

Method used

By designing a high-performance packaging glue for a new energy battery CCS busbar device, a mixture of PA resin and binder is used, and spherical microspheres and nano-aluminum nitride are added to the process to improve the bonding performance and prevent stress shrinkage.

Benefits of technology

The high bonding strength and good sealing performance of polyamide (PA) electronic packaging glue are achieved, cracking and hollowing are avoided, and the flexibility and conductive insulation performance of the packaging glue are improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119662192A_ABST
    Figure CN119662192A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation and packaging process of a high-performance packaging adhesive for a new energy battery CCS busbar device, and belongs to the field of electronic packaging, and the preparation of the electronic packaging adhesive comprises PA resin and a binder, the binder is modified by epoxy resin of polymerized rosin to form a chelating structure cavity, and the chelating structure cavity is formed by the PA resin and the binder. The chelation structure cavity can well form chelation connection with a metal welding leg oxide and a soldering tin oxide or a soldering lead oxide on the electronic component, so that the injection molding electronic packaging adhesive can be well bonded with a metal welding leg on the electronic component. The nano aluminum nitride forms a good conductive insulation barrier in the cavity of the chelation structure by embedding the aluminum metal ions, so that the conductive insulation performance of the injection molding electronic packaging adhesive is greatly improved, and the flexibility of the prepared electronic packaging adhesive is greatly improved. The sealant is good in sealing performance, excellent in insulating performance and good in bonding performance, and injection molding packaging of electronic products can be achieved under the low-temperature and low-pressure conditions.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of electronic packaging, and in particular to a preparation and packaging process of a high-performance packaging adhesive for a CCS busbar device of a new energy battery. Background Art

[0002] Epoxy resin electronic packaging glue is the most commonly used packaging glue method in the packaging glue of new energy battery CCS busbar devices. It has the characteristics of high hardness of the cured product, smooth surface, good gloss, fixation, insulation, waterproof, oil-proof, dust-proof, corrosion-resistant, aging-resistant, and resistant to cold and hot shocks. Epoxy resin electronic packaging glue is usually in liquid state and needs to be injected into the new energy battery CCS busbar device by dispensing. After the dispensing is completed, the epoxy resin electronic packaging glue is cured by heating or ultraviolet light curing. After the new energy battery CCS busbar device is dispensed, the epoxy resin has a high viscosity. The internal pores of the new energy battery CCS busbar device, such as the gaps between the welded pins, are relatively small, and the epoxy resin cannot be completely and quickly filled inside, resulting in internal voids after the epoxy resin is dispensed, making the internal sealing of the electronic components after dispensing poor; the epoxy resin electronic packaging glue is liquid before curing. Therefore, after the new energy battery CCS busbar device is encapsulated by the dispensing method, the epoxy resin part produces an irregular external surface during the flow of the epoxy resin. Under the action of gravity, the epoxy resin will collapse at a high place, so that some protruding parts of the new energy battery CCS busbar device can be completely covered; during the heating and curing process of the epoxy resin electronic packaging glue, the internal gas generated inside the epoxy resin will volatilize and produce bubbles and holes, affecting its internal sealing.

[0003] To address this problem, a technology for encapsulating polyamide (PA) hot melt adhesive materials using a low-temperature and low-pressure injection molding process has been developed. By injection molding on electronic components, the problem of epoxy resin dispensing encapsulating electronic components not being able to be well filled with the epoxy resin and subsequent heating and curing producing bubbles and holes that affect the sealing performance is solved.

[0004] Polyamide (PA) resin is a hot melt adhesive material formed by the polycondensation of dimerized fatty acids and amine compounds. It has the characteristics of fast hot melt curing, strong initial adhesion, solvent resistance, water resistance, high temperature resistance, and low density. It is widely used in low-pressure injection molding of core electronic and electrical components in industries such as automotive electronics, smart homes, and 4G / 5G communications, as well as in wood furniture and other industries. However, electronic packaging molded with polyamide (PA) resin has poor bonding performance, especially when polyamide (PA) resin is used to encapsulate electronic components. The bonding between polyamide (PA) and the metal solder pins of the encapsulated electronic components is poor. In addition, during the cooling process of polyamide (PA) resin injection molding, polyamide (PA) shrinks due to internal stress, resulting in cracking and other defects.

[0005] In summary, the purpose of the present invention is to develop a preparation and packaging process of a high-performance packaging adhesive for a new energy battery CCS busbar device to meet the packaging requirements of good sealing performance, insulation performance and bonding performance. Summary of the invention

[0006] The present invention needs to design a preparation and packaging process of a high-performance packaging adhesive for a new energy battery CCS busbar device, with the aim of solving the problems of the new energy battery CCS busbar device of the prior art made of polyamide (PA) resin injection molding, such as poor bonding performance, cracking caused by shrinkage of the internal stress of the polyamide (PA) during the cooling process of the polyamide (PA) resin injection molding, and the like.

[0007] In order to solve the above technical problems, this application is implemented through the following technical solutions:

[0008] A preparation method for a high-performance packaging adhesive for a CCS busbar device of a new energy battery comprises the following steps:

[0009] Step 1: Preparation of PA resin: Add 60-80 parts of dimer fatty acid and 10-20 parts of fatty dicarboxylic acid by weight to a reactor equipped with nitrogen protection, mix well, add 0.02-0.03 parts of phosphorous acid catalyst and 0.1-0.5 parts of antioxidant, dissolve 10-20 parts of diamine in anhydrous ethanol in a weight ratio of 1:1, and put it into a constant pressure funnel, stir and heat at the same time, when the temperature in the reactor reaches 120-140°C, start to drop diamine, gradually increase the temperature to 160-230°C, react under reflux condensation conditions, and complete the dropwise addition within 1 hour. After the dropwise addition is completed, continue to keep warm for 1 hour, remove the reflux, and under nitrogen protection purge, take the anhydrous ethanol and water out of the reactor by nitrogen, turn off the nitrogen protection, and evacuate at 160-230°C for 30 minutes, pour out in a molten state, cool and granulate to obtain;

[0010] Step 2: Preparation of a binder: Add 50-60 parts of polymerized rosin and 40-50 parts of bisphenol A type high molecular epoxy resin by weight into a reactor under nitrogen protection, heat to 120-140° C. and mix evenly, then add 2-10 parts of 2-methylimidazole and 1-5 parts of 8-hydroxyquinoline, reflux at 160-200° C. for reaction for 2-4 hours, remove the reflux and nitrogen protection, and evacuate at 160-200° C. for 30 minutes, pour out in a molten state, cool, and granulate to obtain the binder;

[0011] Step 3: Mixing of PA resin and binder: 75-85 parts of the PA resin prepared above and 15-30 parts of the binder prepared above are taken by weight, and loaded into a mixer, heated to 160-230° C., melted and stirred, and 1-3 parts of spherical microspheres and 0.5-1 part of nano aluminum nitride are added under stirring conditions, stirred and mixed, and kept for 30 minutes;

[0012] Step 4: Vacuum treatment: Start vacuuming at a temperature of 160-230°C for 1-2 hours until the vacuum degree of the mixer is <200Pa, then stop vacuuming, pour out the molten product and cool it to room temperature, then granulate it to obtain a yellow or brown product.

[0013] Preferably, in step 1, the fatty dicarboxylic acid is a fatty dicarboxylic acid in which the number of carbon atoms between dicarboxylic acids on the main chain is greater than 3 and less than 9.

[0014] Preferably, the fatty dicarboxylic acid is any one of adipic acid, azelaic acid or sebacic acid, or a combination of at least two of them.

[0015] Preferably, in step 1, the diamine is one or a combination of at least two of ethylenediamine, 1,2-propylenediamine, 1,4-butylenediamine, and p-phenylenediamine.

[0016] Preferably, in step 1, the antioxidant is any one of antioxidant 1010, antioxidant 168, and antioxidant BHT, or a combination of at least two of them.

[0017] Preferably, in step 3, the spherical microspheres are porous silica nanospheres with a diameter of 100 to 200 nm.

[0018] Preferably, in step 2, the acid value of the polymerized rosin is 140 mgKOH / g, and the model is B-140.

[0019] Preferably, in step 2, the bisphenol A type high molecular epoxy resin is one of E-12 and E-20.

[0020] The present invention also provides a packaging process of a high-performance packaging adhesive for a new energy battery CCS busbar device, comprising the following steps:

[0021] S1: preheating: placing the electronic packaging glue into a pressurized preheating tank with a pressurized piston, the preheating temperature of the pressurized preheating tank is 160-230° C., so that the low-temperature and low-pressure injection molding electronic packaging glue is in a molten state;

[0022] S2: Product mold loading: Position the packaged new energy battery CCS busbar device in the lower mold cavity of the lower mold, start the preheating device of the lower mold, and make the preheating temperature in the lower mold cavity reach 80-100°C;

[0023] S3: upper mold preheating: start the upper mold preheating device to make the preheating temperature in the upper mold cavity of the upper mold reach 160-230°C;

[0024] S4: Mold closing and injection molding: Start the hydraulic cylinder of the lower mold, the lower mold is lifted and closed with the upper mold, open the pressurizing piston of the pressurizing preheating tank, and control the internal pressure of the pressurizing preheating tank to 1-2.5kgf / cm 2 , open the solenoid valve, and the molten electronic packaging glue in the pressurized preheating tank enters multiple injection ports through the injection connection pipe with a thermal insulation layer. When the electronic packaging glue passes through multiple injection ports, it is further heated by the upper mold and injected into the mold cavity formed between the upper mold and the lower mold. The internal pressure of the pressurized preheating tank is controlled so that the pressure at the injection port reaches 20-50kgf / cm 2 , and keep it for 15 to 30 seconds, then close the solenoid valve;

[0025] S5: Cooling molding: Turn on the upper mold cooling device to cool the upper mold to 80-100°C, open the mold and take it out.

[0026] In the present invention, during the preparation process of PA resin, a fatty dicarboxylic acid is used as the main chain, and the number of carbon atoms between the dicarboxylic acids is greater than 3 and less than 9, especially a dicarboxylic acid in adipic acid, azelaic acid or sebacic acid. The fatty dicarboxylic acid and diamine are condensed to form a cyclic cavity structure with more than 6 members, and the cavity structure can form a good bonding effect with the binder.

[0027] The present invention utilizes the adhesive to greatly improve the bonding performance of polyamide (PA) electronic packaging adhesive. Since the polymerized rosin in the adhesive has good flexibility after being modified by epoxy resin, the flexibility of the polyamide (PA) electronic packaging adhesive is further improved.

[0028] The present invention utilizes the binder and 8-hydroxyquinoline. The -OH in the -NCC-OH structure of 8-hydroxyquinoline has great chemical activity. The -OH in the -NCC-OH structure can undergo esterification reaction and cross-linking with the -COOH structure in rosin acid. Since the polymerized rosin structure contains multiple ring structures, 8-hydroxyquinoline also has a ring structure. After the polymerized rosin and 8-hydroxyquinoline undergo esterification reaction, the ring structure of the polymerized rosin structure and the ring structure of 8-hydroxyquinoline form a chelate structure cavity. The chelate structure cavity can well form a chelate connection with the metal solder pin oxide and solder oxide or solder lead oxide on the connector of the CCS busbar device during injection molding, so that the injection-molded electronic packaging adhesive can also be well bonded with the metal solder pin on the connector of the CCS busbar device.

[0029] In the present invention, nano aluminum nitride is added, and aluminum metal ions of the nano aluminum nitride are embedded in a chelate structure cavity formed by the ring structure of the polymerized rosin structure and the ring structure of 8-hydroxyquinoline in a chelate manner. The aluminum metal ions of the nano aluminum nitride are embedded in a ring cavity structure with more than 6 members formed by the condensation reaction of aliphatic dicarboxylic acid and diamine in a chelate manner, which not only makes the nano aluminum nitride form a good conductive insulation barrier, thereby greatly improving the conductive insulation performance of the injection-molded electronic packaging adhesive, but also greatly improves the flexibility of the prepared electronic packaging adhesive.

[0030] In the present invention, by adding spherical microspheres, the electronic product can well prevent the internal stress of polyamide (PA) from shrinking and cracking during the process of cooling and molding the electronic packaging glue during injection molding of the electronic product.

[0031] The electronic packaging adhesive prepared by the present invention can be injected at a relatively low injection temperature of 160 to 230°C and a relatively low injection pressure of 20 to 50 kgf / cm 2 The invention realizes the encapsulation and sealing injection molding of electronic products, solves the injection molding problem of polyamide (PA) and improves the bonding strength problem of injection molding of polyamide (PA) compared with the prior art. BRIEF DESCRIPTION OF THE DRAWINGS

[0032] Figure 1 (a) is the internal cross-sectional effect formed by injection molding and curing at the connector PIN top and PIN foot area of ​​the CCS busbar device in Example 4.

[0033] Figure 1 (b) is the internal cross-sectional effect formed by injection molding and curing at the connector PIN top and PIN foot area of ​​the CCS busbar device in Example 5.

[0034] Figure 2 (a) is the internal cross-sectional effect formed by injection molding and curing at the connector PIN top and PIN foot area of ​​the CCS busbar device in comparative example 3.

[0035] Figure 2 (b) is the internal cross-sectional effect formed by injection molding and curing at the connector PIN top and PIN foot area of ​​the CCS busbar device in comparative example 4.

[0036] Figure 3 (a) is the internal cross-sectional effect formed by injection molding and curing in the NTC interior and surface area of ​​the CCS busbar device in Example 6.

[0037] Figure 3 (b) is the internal cross-sectional effect formed by injection molding and curing in the NTC interior and surface area of ​​the CCS busbar device in Example 7.

[0038] Figure 4 (a) is the internal cross-sectional effect formed by injection molding and curing in the NTC interior and surface area of ​​the CCS busbar device in comparative example 5.

[0039] Figure 4 (b) is the internal cross-sectional effect formed by injection molding and curing of the NTC inside and surface area of ​​the CCS busbar device in comparative example 6.

[0040] Figure 5 It is a schematic diagram of the injection molding process of the electronic packaging adhesive of the present invention.

[0041] exist Figure 5 The markings are: 1-pressurized preheating tank, 2-pressurized piston, 3-injection connecting pipe, 4-insulation layer, 5-solenoid valve, 6-upper mold, 6a-upper mold cavity, 7-lower mold, 7a-lower mold cavity, 7b-glue injection port, 8-hydraulic cylinder. DETAILED DESCRIPTION

[0042] The present invention is further described in detail below in conjunction with the embodiments. It should also be understood that the following embodiments are only used to further illustrate the present invention and cannot be construed as limiting the scope of protection of the present invention. The specific quality, reaction time and temperature, process parameters, etc. in the examples are only examples within the appropriate ranges. Some non-essential improvements and adjustments made by those skilled in the art according to the above content of the present invention all belong to the scope of protection of the present invention.

[0043] All reagents used were commercial reagents unless otherwise specified and were not further purified before use.

[0044] Example 1

[0045] A preparation method for a high-performance packaging adhesive for a CCS busbar device of a new energy battery comprises the following steps:

[0046] Step 1: Preparation of PA resin: 227.50 g of dimer acid DM-70 and 48.75 g of adipic acid were added by weight to a reactor under nitrogen protection, 0.065 g of phosphorous acid catalyst and 1.04 g of antioxidant 1010 were added after mixing, 47.65 g of ethylenediamine was dissolved in anhydrous ethanol in a weight ratio of 1:1, and loaded into a constant pressure funnel, stirred and heated at the same time, when the temperature in the reactor reached 130°C, diamine was added dropwise, and the temperature was gradually increased to 180°C, and the reaction was carried out under reflux condensation conditions, and the addition was completed within 1 hour. After the addition was completed, the temperature was kept warm for 1 hour, the reflux was removed, and under nitrogen protection purging, anhydrous ethanol and water were taken out of the reactor by nitrogen, the nitrogen protection was turned off, and vacuum was drawn at 180°C for 30 minutes, and the molten state was poured out and cooled and granulated to obtain the above product, which was recorded as PA-01;

[0047] Step 2: Preparation of binder: 112.50 g of polymerized rosin B-140 with an acid value of 140 mgKOH / g and 92.25 g of bisphenol A type high molecular epoxy resin E-12 were added by weight into a reactor under nitrogen protection, and heated to 120-140° C. and mixed evenly, and then 13.52 g of 2-methylimidazole and 6.75 g of 8-hydroxyquinoline were added and refluxed at 180° C. for reaction for 3 h, and the reflux and nitrogen protection were removed, and vacuum was drawn at 180° C. for 30 min, and the molten state was poured out and cooled and granulated to obtain the product, which was recorded as RB-01;

[0048] Step 3: Mixing of PA resin and binder: Take 259.20g of PA resin PA-01 and 35.56g of binder RB-01, put them into a mixer, heat to 180°C, melt and stir, add 4.50g of porous silica nanospheres with a diameter of 100-200nm and 1.69g of nano aluminum nitride under stirring, stir and mix, and keep for 30min;

[0049] Step 4: Vacuum treatment: Start vacuuming at 180°C for 2 hours until the vacuum degree of the mixer is <200Pa, then stop vacuuming and cool down to 160°C. Pour out the molten product and cool it to room temperature before granulating to obtain a yellow or brown product, which is recorded as FZ-01.

[0050] Examples 2 to 5 were prepared according to the formula ingredients of the electronic packaging adhesive in each example in Table 1, and the preparation was carried out in the same manner as in Example 1.

[0051] Comparative Example 1

[0052] A preparation of a high-performance packaging adhesive for a new energy battery CCS busbar device. The preparation of the PA resin is the same as that of PA-01 in Example 1, except that no binder is added in step 3. 260 g of the PA resin PA-01 is heated to 180° C. and stirred in a molten state. 4.50 g of porous silica nanospheres with a diameter of 100 to 200 nm and 1.69 g of nano-aluminum nitride are added under stirring. The mixture is stirred and kept for 30 minutes. The same as step 4 in Example 1 is used to prepare a comparative electronic packaging adhesive. The above product is recorded as FZ-A.

[0053] Comparative Example 2

[0054] A high-performance packaging adhesive for a new energy battery CCS busbar device is prepared. The preparation of PA resin is the same as PA-01 in Example 1, and the preparation of adhesive is the same as RB-01 in Example 1. The difference from Example 1 is that only adhesive and PA resin are added in step 3, and spherical microspheres and nano-aluminum nitride are not added. The same as step 4 of Example 1 is used to prepare a comparative electronic packaging adhesive. The above product is recorded as FZ-B.

[0055] Table 1

[0056]

[0057] Performance Test:

[0058] The electronic packaging adhesive prepared in Examples 1 to 3 and Comparative Examples 1 to 2 was tested as follows:

[0059] Softening point test: Use SYD-4507 petroleum asphalt softening point tester and test according to standard GB / T15332-94.

[0060] Melt viscosity test: using NDJ-8S rotary viscometer coating viscometer, the sample is placed in a container with a heating device, heated and maintained at a melt temperature of 200°C for testing.

[0061] Peel strength test: Test the peel strength between metal iron and PVC, i.e. s-PVC. Melt the electronic packaging glue and apply it on the surface of PVC and iron respectively; then heat the PVC and iron plate at 150℃ and 10kgf / cm 2 Under pressure, press for 1 minute; sample specifications: 120×25×0.2mm, test interval length greater than 50mm. After the sample is placed under test conditions for 24 hours, the peel strength performance test is carried out on a GT-AI-3000 tensile testing machine. Test speed: 50mm / min.

[0062] Glass transition temperature: Refer to GB / T11998-1989 Determination of glass transition temperature of plastics - Thermomechanical analysis method.

[0063] Shear strength test: refer to GB 7124-86 Adhesive tensile shear strength test method.

[0064] Dielectric constant test: The dielectric constant of electronic packaging glue is measured by microwave method using STD-A dielectric constant tester.

[0065] Water vapor transmission rate test: According to the national standard GB / T1037-2021 Determination of water vapor transmission performance of plastic films and sheets, use a plastic film moisture permeability cup to make the encapsulation glue into a uniform rectangular sheet, accurately measure the length, width and thickness of the sheet (accurate to 0.01mm), and calculate the surface area (unit: m 2), placed in a constant temperature and humidity chamber, set the temperature to 38 ± 0.6 ° C, relative humidity to 90 ± 2%, and use the weight gain method to measure the increase in weight of the sheet when the exposure time is 1 day, 2 days, 3 days, 4 days, and 5 days (accurate to 0.0001g). The average value is divided by the surface area of ​​the sheet to obtain the water vapor permeability value.

[0066] The test results of Examples 1 to 3 and Comparative Examples 1 to 2 are shown in Table 2.

[0067] Table 2

[0068]

[0069] According to the above test data, in the preparation of a high-performance packaging adhesive for a new energy battery CCS busbar device prepared by the present invention, in Examples 1 to 3, after the PA resin is added and mixed with a binder, the softening point of the material is between 150 and 200°C. Compared with Comparative Example 1, which does not use a binder, although the softening point of the material becomes higher, the softening point of the material is within 200°C, which can still meet the requirements of low-temperature injection molding.

[0070] After the PA resin is mixed with the binder, the viscosity increases, the peel strength is significantly improved, and the surface bonding strength increases. This is due to the use of 8-hydroxyquinoline in the binder. The -OH in the -NCC-OH structure of 8-hydroxyquinoline has greater chemical activity. The -OH in the -NCC-OH structure can undergo esterification reaction and cross-linking with the -COOH structure in rosin acid. Since the polymerized rosin structure contains multiple ring structures, 8-hydroxyquinoline also has a ring structure. After the polymerized rosin and 8-hydroxyquinoline are esterified, the ring structure of the polymerized rosin structure and the ring structure of 8-hydroxyquinoline form a chelate structure cavity. The chelate structure cavity can form a chelate connection with the metal solder foot oxide and solder oxide or solder lead oxide on the connector of the CCS busbar device during injection molding, so that the injection-molded electronic packaging adhesive can also be well bonded to the metal solder foot on the connector of the CCS busbar device.

[0071] The electronic packaging adhesive prepared by the present invention has a relatively lower glass transition temperature, indicating that it has better low-temperature resistance.

[0072] In Examples 1 to 3, the dielectric constant ε0 (25°C) is lower than that in Comparative Examples 1 and 2, indicating that the electronic packaging adhesive prepared by the present invention has more excellent electrical insulation performance. This is because nano-aluminum nitride is added to the electronic packaging adhesive, and the aluminum metal ions of the nano-aluminum nitride are embedded in the ring structure of the polymerized rosin structure and the ring structure of 8-hydroxyquinoline to form a chelate structure cavity, and the aluminum metal ions of the nano-aluminum nitride are embedded in a 6-membered ring cavity structure formed by the condensation reaction of aliphatic dicarboxylic acid and diamine by chelation, which not only makes the nano-aluminum nitride form a good conductive insulation barrier, thereby greatly improving the conductive insulation performance of the injection-molded electronic packaging adhesive, but also greatly improves the flexibility of the prepared electronic packaging adhesive.

[0073] The electronic packaging adhesive prepared by the present invention has a lower water vapor transmission value than that of Comparative Example 1 and Comparative Example 2, indicating that the electronic packaging adhesive prepared by the present invention has better water sealing performance.

[0074] Example 4

[0075] Reference Figure 5 , a packaging process of a high-performance packaging adhesive for a new energy battery CCS busbar device, comprising the following steps:

[0076] S1: Preheating: The electronic packaging glue FZ-01 prepared in Example 1 is placed in a pressurized preheating tank 1 with a pressurized piston 2. The preheating tank 1 is usually arranged with a circular cross section. The preheating temperature of the pressurized preheating tank 1 is 180° C., so that the electronic packaging glue FZ-01 is in a molten state;

[0077] S2: Product mold loading: Position the packaged electronic product in the lower mold cavity 7a of the lower mold 7, the packaged electronic product is a PIN pin connector with a new energy battery CCS busbar device, start the preheating device of the lower mold 7, and make the preheating temperature in the lower mold cavity 7a reach 80-100°C;

[0078] S3: upper mold preheating: start the preheating device of the upper mold 6 to make the preheating temperature in the upper mold cavity 6a of the upper mold 6 reach 200°C;

[0079] S4: Mold closing and injection molding: Start the hydraulic cylinder 8 of the lower mold 7, the lower mold 7 is lifted and closed with the upper mold 6, open the pressurizing piston 2 of the pressurizing preheating tank 1, and control the internal pressure of the pressurizing preheating tank 1 to 1.5kgf / cm 2, open the solenoid valve 5, the molten electronic packaging glue FZ-01 in the pressurized preheating tank 1 enters the multiple injection ports 7b through the injection connecting pipe 3 with the insulation layer 4, and the electronic packaging glue FZ-01 is further heated by the upper mold 6 when passing through the multiple injection ports 7b. After further heating, the temperature of the electronic packaging glue FZ-01 increases by 10 to 30°C, and the fluidity of the electronic packaging glue FZ-01 is better, and it is injected into the mold cavity formed between the upper mold 6 and the lower mold 7. Since the injection port 7b is set to a circular cross-section, the number of the injection ports 7b is set to 5, and the opening diameter of the injection port 7b is 0.1 of the opening diameter of the heating preheating tank 1, so that by controlling the internal pressure of the pressurized preheating tank 1, the pressure of the injection port 7b reaches 30kgf / cm 2 , and keep it for 15 to 30 seconds, then close the solenoid valve 5.

[0080] S5: Cooling and molding: Turn on the cooling device of the upper mold 6, so that the upper mold 6 is cooled to the same temperature as the lower mold 7, 80-100°C, and then the mold is opened and taken out.

[0081] The appearance of the injection molded product has no cracks, no voids, and no collapse. The inside of the injection molded product was cut and magnified 10 times and photographed. Figure 1 (a) is the effect diagram shown.

[0082] The injection molded product is subjected to a 500H hot and cold shock test. The test method is as follows: the injection molded product is placed in a hot and cold shock test chamber, and subjected to 500 cycles of temperature shock (-40℃ for 30min, 125℃ for 30min, switching time ≤30s, this is 1 cycle, and 500 cycles are performed). After the test, the appearance of the injection molded product is not affected, and there is no sign of deterioration, cracks, or deformation.

[0083] The injection molded products are subjected to a 500H water immersion test with electricity. The test method is as follows: the injection molded product components are immersed in 25℃±7℃ water for 500h, and the sealing conditions of the injection molded products are observed during this time period. After the test, the appearance of the injection molded products is not affected, and there are no signs of deterioration, cracks, or deformation.

[0084] Example 5

[0085] The steps are the same as those in Example 4, except that the electronic packaging adhesive FZ-02 prepared in Example 2 is used, and the internal pressure of the pressurized preheating tank 1 is controlled to be 2.5 kgf / cm 2 , so that the pressure of the injection port 7b reaches 50kgf / cm 2The preheating temperature of the pressurized preheating tank 1 is 200℃, and the preheating temperature of the upper mold is 220℃. The appearance of the product after injection molding has no cracks, no voids, and no collapse. The internal structure of the injection molded product is cut and magnified 10 times and photographed. Figure 1 The injection molded product was subjected to a 500-hour thermal shock test and a 500-hour live water immersion test. The test results are shown in Table 3.

[0086] Example 6

[0087] The same as Example 4, the electronic packaging glue FZ-01 prepared in Example 1 is used, the difference is that the encapsulated electronic product is the thermistor NTC of the CCS busbar device of the new energy battery, and the appearance of the product after injection molding has no cracks, no voids, and no collapse. The inside of the injection molded product is cut and magnified 10 times and photographed to obtain Figure 3 The injection molded product was subjected to a 500-hour thermal shock test and a 500-hour live water immersion test. The test results are shown in Table 3.

[0088] Example 7

[0089] Same as Example 5, except that the packaged electronic product is a thermistor NTC of a new energy battery CCS busbar device. After injection molding, the appearance of the product has no cracks, no voids, and no collapse. The inside of the injection molded product is cut and magnified 10 times and photographed to obtain Figure 3 The injection molded product was subjected to a 500-hour thermal shock test and a 500-hour live water immersion test. The test results are shown in Table 3.

[0090] Comparative Example 3

[0091] The same as Example 4, except that the electronic packaging adhesive uses FZ-A prepared in Comparative Example 1, the inside of the injection molded product is cut and magnified 10 times and photographed to obtain Figure 2 The injection molded product was subjected to a 500-hour thermal shock test and a 500-hour live water immersion test. The test results are shown in Table 3.

[0092] Comparative Example 4

[0093] The same as Example 4, except that the electronic packaging adhesive used is FZ-B prepared in Comparative Example 2. The appearance of the product after injection molding has no cracks, no voids, and no collapse. The inside of the injection molded product is cut and magnified 10 times and photographed to obtain Figure 2 The injection molded product was subjected to a 500-hour thermal shock test and a 500-hour live water immersion test. The test results are shown in Table 3.

[0094] Comparative Example 5

[0095] The same as Example 6, except that the electronic packaging adhesive uses FZ-A prepared in Comparative Example 1. The appearance of the product after injection molding has no cracks, no voids, and no collapse. The inside of the injection molded product is cut and magnified 10 times and photographed to obtain Figure 4 The injection molded product was subjected to a 500-hour thermal shock test and a 500-hour live water immersion test. The test results are shown in Table 3.

[0096] Comparative Example 6

[0097] The same as Example 7, except that the electronic packaging adhesive used was FZ-B prepared in Comparative Example 2. The appearance of the product after injection molding had no cracks, no voids, and no collapse. The inside of the injection molded product was cut and magnified 10 times and photographed to obtain Figure 4 The injection molded product was subjected to a 500-hour thermal shock test and a 500-hour live water immersion test. The test results are shown in Table 3.

[0098] The test results of Examples 1 to 3 and Comparative Examples 1 to 2 are shown in Table 3.

[0099] Table 3

[0100]

[0101] from Figure 1-Figure 2 It can be seen that under low temperature and low pressure conditions, the electronic packaging glue has no adverse conditions such as bubbles, cavities and collapse after curing of epoxy resin electronic packaging glue after injection molding. The packaging effect of injection molding is good. Figure 1 and Figure 2 Further comparison shows that the electronic packaging glue of the present invention is more compact and has better sealing performance. In addition, the electronic packaging glue is tightly bonded to the metal pins. Figure 2 In (a), there are some large white spots, which are caused by the fact that the filled spherical microspheres or nano-aluminum nitride cannot be filled and dispersed through the chelated cavity structure on the binder because the spherical microspheres or nano-aluminum nitride are not added to the binder in Comparative Example 1. Figure 2 In (b), there are multiple collapsed bubble points. This is because no spherical microspheres or nano-aluminum nitride were added in Comparative Example 2, and the electronic packaging adhesive cooled and shrank unevenly after injection molding, resulting in local collapse. This further illustrates that spherical microspheres or nano-aluminum nitride can effectively prevent the internal stress of polyamide (PA) from shrinking and cracking during the cooling process of the electronic packaging adhesive injection molding and mold opening.

[0102] pass Figure 3 and Figure 4 By comparison, under low temperature and low pressure conditions, for the thermistor NTC of the encapsulated new energy battery CCS busbar device, the encapsulation resin of the present invention has a very obvious injection molding effect, and the internal filling is uniform without white spots.

[0103] According to the test data in Table 3, the high-performance packaging glue for the CCS busbar device of a new energy battery prepared by the present invention can meet the packaging requirements of new energy batteries in terms of appearance, 500H hot and cold shock test, and 500H charged water immersion after injection molding of the product.

[0104] The above embodiments only express the implementation methods of the present invention, and the descriptions thereof are relatively specific and detailed, but they cannot be understood as limiting the scope of the present invention. It should be pointed out that, for those of ordinary skill in the art, several variations and improvements can be made without departing from the concept of the present invention, and these all belong to the protection scope of the present invention.

Claims

1. Preparation of high-performance packaging glue for CCS busbar devices of new energy batteries, characterized in that: The steps include: Step 1: Preparation of PA resin: Add 60-80 parts of dimer fatty acid and 10-20 parts of fatty dicarboxylic acid by weight to a reactor equipped with nitrogen protection, mix well, add 0.02-0.03 parts of phosphorous acid catalyst and 0.1-0.5 parts of antioxidant, dissolve 10-20 parts of diamine in anhydrous ethanol in a weight ratio of 1:1, and put it into a constant pressure funnel, stir and heat at the same time, when the temperature in the reactor reaches 120-140°C, start to drop diamine, gradually increase the temperature to 160-230°C, react under reflux condensation conditions, and complete the dropwise addition within 1 hour. After the dropwise addition is completed, continue to keep warm for 1 hour, remove the reflux, and under nitrogen protection purge, take the anhydrous ethanol and water out of the reactor by nitrogen, turn off the nitrogen protection, and evacuate at 160-230°C for 30 minutes, pour out in a molten state, cool and granulate to obtain; Step 2: Preparation of a binder: Add 50-60 parts of polymerized rosin and 40-50 parts of bisphenol A type high molecular epoxy resin by weight into a reactor under nitrogen protection, heat to 120-140°C and mix evenly, then add 2-10 parts of 2-methylimidazole and 1-5 parts of 8-hydroxyquinoline, reflux at 160-200°C for reaction for 2-4 hours, remove the reflux and nitrogen protection, and evacuate at 160-200°C for 30 minutes, pour out in a molten state, cool, and granulate to obtain the binder; Step 3: Mixing of PA resin and binder: 75-85 parts of the PA resin prepared above and 15-30 parts of the binder prepared above are taken by weight, and loaded into a mixer, heated to 160-230° C., melted and stirred, and 1-3 parts of spherical microspheres and 0.5-1 parts of nano aluminum nitride are added under stirring conditions, and the mixture is stirred and kept for 30 minutes; Step 4: Vacuum treatment: Start vacuuming at a temperature of 160-230°C for 1-2 hours until the vacuum degree of the mixer is <200Pa, then stop vacuuming, pour out the molten product, cool it to room temperature, and then granulate it to obtain a yellow or brown product.

2. According to claim 1, the preparation of a high-performance packaging adhesive for a new energy battery CCS busbar device is characterized in that: In step 1, the fatty dicarboxylic acid is a fatty dicarboxylic acid in which the number of carbon atoms between dicarboxylic acids on the main chain is greater than 3 and less than 9.

3. According to claim 1, the preparation of a high-performance packaging adhesive for a new energy battery CCS busbar device is characterized in that: In step 1, the fatty dicarboxylic acid is any one of adipic acid, azelaic acid or sebacic acid, or a combination of at least two of them.

4. According to claim 1, the preparation of a high-performance packaging adhesive for a new energy battery CCS busbar device is characterized in that: In step 1, the diamine is one of ethylenediamine, 1,2-propylenediamine, 1,4-butylenediamine, and p-phenylenediamine, or a combination of at least two of them.

5. According to claim 1, the preparation of a high-performance packaging adhesive for a new energy battery CCS busbar device is characterized in that: In step 1, the antioxidant is any one of antioxidant 1010, antioxidant 168, and antioxidant BHT, or a combination of at least two of them.

6. According to claim 1, the preparation of a high-performance packaging adhesive for a new energy battery CCS busbar device is characterized in that: In step 3, the spherical microspheres are porous silica nanospheres with a diameter of 100-200 nm.

7. The preparation of a high-performance packaging adhesive for a new energy battery CCS busbar device according to claim 1, characterized in that: In step 2, the acid value of the polymerized rosin is 140 mgKOH / g, and the model is B-140.

8. The preparation of a high-performance packaging adhesive for a new energy battery CCS busbar device according to claim 1, characterized in that: In step 2, the bisphenol A type high molecular epoxy resin model is one of E-12 and E-20.

9. A packaging process for a high-performance packaging adhesive for a new energy battery CCS busbar device as claimed in claims 1-8, characterized in that: The following steps are involved: S1: preheating: placing the electronic packaging glue into a pressurized preheating tank with a pressurized piston, the preheating temperature of the pressurized preheating tank is 160-230° C., so that the low-temperature and low-pressure injection molding electronic packaging glue is in a molten state; S2: Product mold loading: Position the packaged new energy battery CCS busbar device in the lower mold cavity of the lower mold, start the preheating device of the lower mold, and make the preheating temperature in the lower mold cavity reach 80~100℃; S3: Upper mold preheating: Start the upper mold preheating device to make the preheating temperature in the upper mold cavity of the upper mold reach 160~230℃; S4: Mold closing and injection molding: Start the hydraulic cylinder of the lower mold, the lower mold is lifted and closed with the upper mold, open the pressurizing piston of the pressurizing preheating tank, and control the internal pressure of the pressurizing preheating tank to 1~2.5kgf / cm 2 , open the solenoid valve, and the molten electronic packaging glue in the pressurized preheating tank enters multiple injection ports through the injection connection pipe with a thermal insulation layer. When the electronic packaging glue passes through multiple injection ports, it is further heated by the upper mold and injected into the mold cavity formed between the upper mold and the lower mold. The internal pressure of the pressurized preheating tank is controlled so that the pressure at the injection port reaches 20~50kgf / cm 2 , and keep it for 15~30s, then close the solenoid valve; S5: Cooling molding: Turn on the upper mold cooling device to cool the upper mold to 80~100℃, open the mold and take it out.